2019
DOI: 10.1016/j.iccn.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s experiences of their child’s withdrawal syndrome: a driver for reciprocal nurse-parent partnership in withdrawal assessment

Abstract: Facilitating nurse-parent collaboration in withdrawal assessment may have reciprocal benefits by moderating parental stress and aiding the assessment and management of withdrawal syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Assessment of IWS, as we observed, is more common PICU practice with only two validated tools (28, 29); however, it is rarely studied in adults and thus not part of the ABCDEF bundle (30). The presence of IWS is stressful for the critically ill child and their parents (31) and leads to prolonged hospital stay and increased healthcare costs (32); thus, addition of IWS to the ABCDEF bundle must be considered particularly for pediatrics. We also found that sedation protocols were implemented in daily practice in half of PICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of IWS, as we observed, is more common PICU practice with only two validated tools (28, 29); however, it is rarely studied in adults and thus not part of the ABCDEF bundle (30). The presence of IWS is stressful for the critically ill child and their parents (31) and leads to prolonged hospital stay and increased healthcare costs (32); thus, addition of IWS to the ABCDEF bundle must be considered particularly for pediatrics. We also found that sedation protocols were implemented in daily practice in half of PICUs.…”
Section: Discussionmentioning
confidence: 99%
“…The comfort provided to families will enhance a better understanding of their child's behavior and prospectively contribute to the success of analgo-sedative pain assessment and management plans. 36 In future, artificial intelligence (AI) may also emerge as a useful technology to improve the evaluation and management of neonatal analgesic and sedative use. AI can potentially reduce the manual workload of collecting subjective information intermittently through the continuous retrieval of data through the use of AI leading to improved recognition and management of neonatal analgo-sedative requirements Even though there is limited information available concerning IWS epidemiology specifically for the neonatal group, data from the general pediatric population shows high prevalence and incidence rates for this problem particularly when drug exposure lasts more than 5 days.…”
Section: Preventionmentioning
confidence: 99%
“…The comfort provided to families will enhance a better understanding of their child's behavior and prospectively contribute to the success of analgo-sedative pain assessment and management plans. 36…”
Section: Preventionmentioning
confidence: 99%
“…This will help center the patient/family as partners in care, mitigate anxiety and psychological stress, and allow them to participate in identifying symptoms of iatrogenic withdrawal. 14…”
Section: Components Of a Sedation Weaning Strategymentioning
confidence: 99%